Post-Keynesian macrodynamics and path-dependent growth - Mark Setterfield (Intervention. European Journal of Economics and Economic Policies, 2011)
This paper discusses the treatment of growth as a path-dependent process in post-Keynesian macrodynamics. A synthetic post-Keynesian growth model is used to demonstrate the ways in which growth can be described as path-dependent in the post-Keynesian tradition. Recent developments in neoclassical endogenous growth theory are then discussed, with a view to highlighting the sense in which these developments encroach on the post-Keynesian treatment of growth as demand-led and path-dependent. Finally, the paper reflects on the pros and cons of these neoclassical developments for the future of post-Keynesian macrodynamics.
Keywords: E12; E13; O41; 330; post-Keynesian growth theory; neoclassical growth theory; endogenous growth; path dependence